Effect of Prolong Exposure to Gas Flaring on some Haematological Parameters of Humans in the Niger Delta Region of Nigeria - Adienbo, OM; NwafoR, A (Journal of Applied Sciences and Environmental Management, 2010)
The objective of this study was to examine the deterioration effect, if any, of prolonged exposure to gas flaring on hematological parameters. Subjects for the study were drawn from the represented groups in the oil and gas production environments and compared to the non gas flaring environment. Venous blood samples were collected from the subjects and analysed for PCV, Hb, RBC and WBC counts, and red cell morphology. The result showed that the PVC, Hb and RBC count respectively reduced, WBC count and abnormal red cell morphology increased, compared to control (p